Intermittent documentation of blood pressure values does not provide comprehensive evaluation of the hemodynamic response during continuous intravenous medication administration - Brittany R. Doyle; Emerson B. Nairon; Erica Jones; Amber Salter; DaiWai M. Olson (Scientific Reports)
Abstract Blood pressure (BP) is a dynamic measure that is frequently discussed in static terms. There exist many limitations in current documentation systems whereby documented BP values may not be reflective of the dynamic variability of BP. This study used an observational, prospective, non-randomized study design to examine the variability in BP response during intravenous vasoactive medication administration in an intensive care unit setting. Subjects admitted to a neuroscience intensive care unit were monitored continuously during a 12-hour period. The BP values include systolic BP, diastolic BP, and mean arterial pressure. Intermittent values from an intra-arterial figurecatheter (a-line) and continuously sampled values from an a-line obtained using continuous data acquisition (CDA) software, were compared to intermittently sampling of cuff-based BP measurements documented in the medical record. The 30 patients provided 1,220,511 BP observations from CDA, 944 from a-line documentation, and 416 from cuff-based BP documentation. The systolic BP was used as a goal parameter for 23 (77%) of the patients. Repeated measures models demonstrated that on average cuff-based differed from intermittent a-line and from CDA (p < .005) for all BP values. No differences between a-line and CDA were observed. Concordance correlation coefficients ranged from 0.56 to 0.72 for a-line, cuff-based BP, and CDA, indicating moderate agreement. Using intermittently documented BP values does not fully represent the dynamic nature of BP over time.